The association between long working hours, shift work, and suicidal ideation: A systematic review and meta-analyses - Joungsue Kim; Ria Kwon; Hyunok Yun; Ga-Young Lim; Kyung-Sook Woo; Inah Kim (Nordic Association of Occupational Safety and Health (NOROSH), 2024)
OBJECTIVES: The association between occupational psychosocial factors and mental health has been studied in several systematic reviews. However, few systematic reviews exist that specifically address suicidal ideation. Therefore, this systematic review and meta-analysis aimed to examine the associations between long working hours, shift work, and suicidal ideation. METHODS: We systematically screened and collected studies published between January 1970 and September 2022 from three electronic databases and Google Scholar. We conducted a meta-analysis using a random-effects model and assessed the risk of bias using a navigation guide. Additionally, the grading of recommendations assessment, development and evaluation (GRADE) approach was used to consider five items, including the risk of bias and publication bias. RESULTS: Twenty-eight articles were included in this meta-analysis. After adjusting for covariates, the overall odds ratio (OR) for long working hours and shift work were 1.44 [95% confidence interval (CI) 1.26-1.63] and 1.34 (95% CI 1.22-1.47), respectively. Compared with those who worked <40 hours per week, those who worked >55 hours per week had a 1.65 (95% CI 1.37-1.98) higher risk of suicidal ideation, and fixed night shift workers had 1.37 (95% CI 1.03-1.83) higher risk than non-shift workers. CONCLUSIONS: Evidence has shown associations between long working hours, shift work, and suicidal ideation. Implementing evidence-based interventions to address these risk factors may help prevent the progression of suicidal ideation. However, further studies are critically needed, especially those using standardized exposure definitions and longitudinal data.